Text Pin: Improving text selection with mode-augmented handles on touchscreen mobile devices. Issue 175 (July 2023) - Tu, Huawei; Gao, Boyu; Wu, Huiyue; Lyu, Fei
Abstract: Text selection is a required step prior to performing many text editing tasks like copy or cut. Text selection relying on adjustment handles is a widely adopted method on touchscreen mobile devices. However, this method has limitations like slow and unconformable interactions when dragging handles and poor performance of selecting non-adjacent text for editing as one. To address these limitations, this study proposes Text Pin, a novel technique that specifies the two ends of intended text by finger tapping rather than finger dragging. We conducted three pilot studies to design Text Pin and an experiment to evaluate its performance. Experimental results show Text Pin (M = 11.49 s) was generally faster than the default handle-based technique on Android (M = 14.95 s) by 23.14% and a gesture-based technique ( Fix & Slide ) (M = 14.41 s) by 20.26% while having similar selection accuracy ( Text Pin vs the default technique vs Fix & Slide : 0.95 vs 0.94 vs 0.95). Our study consequently demonstrates the potential of Text Pin as a suitable alternative to existing handle-based text selection techniques on touchscreen mobile devices. Highlights: This study proposes Text Pin, a novel text selection technique for direct-finger touch interactions. Text Pin specifies the two ends of intended text by finger tapping rather than finger dragging. Text Pin supports efficient selection of non-adjacent text for editing as one. Results show that Text Pin is an effective text selection technique and can be a viable alternative to current handle-based techniques on touchscreen mobile devices.